Turbulence and tranquillity - Jalil, Azizul, 1933- (Dhaka : University Press, 2006)
Autobiographical reminiscences of Pakistan civil servant.
Keywords: Jalil, Azizul, -- 1933-; World Bank -- Officials and employees -- Biography; Pakistan -- Officials and employees -- Biography